2005
DOI: 10.1037/0022-0167.52.3.400
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Cramer's (1999) Help-Seeking Model and Acculturation Effects With Asian and Asian American College Students.

Abstract: The generalizability of K. M. Cramer's (1999) help-seeking model was examined for Asian and Asian American college students. The construct of acculturation was then added to Cramer's model to determine if it would improve the model fit. Asian and Asian American (n ϭ 202) students completed help-seeking measures and behavioral and value-based measures of acculturation. White (n ϭ 336) students completed only help-seeking measures. Although path analyses showed that Cramer's model fit both samples, structural in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
152
8
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(180 citation statements)
references
References 52 publications
16
152
8
4
Order By: Relevance
“…The Japanese international student group was expected to have greater self-concealment, because the ability to control emotions and the ability to resolve psychological problems without aid are viewed as virtues in Asian cultures, including Japanese culture (Kim, Atkinson, & Yang, 1999). Nevertheless, our results suggest that there is a universal nature of self-concealment, as found in previous studies (e.g., Liao, Rounds, & Klein, 2005). As predicted, gender was not a variable related to the attitudes measured here.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The Japanese international student group was expected to have greater self-concealment, because the ability to control emotions and the ability to resolve psychological problems without aid are viewed as virtues in Asian cultures, including Japanese culture (Kim, Atkinson, & Yang, 1999). Nevertheless, our results suggest that there is a universal nature of self-concealment, as found in previous studies (e.g., Liao, Rounds, & Klein, 2005). As predicted, gender was not a variable related to the attitudes measured here.…”
Section: Discussioncontrasting
confidence: 62%
“…A third limitation is that no data were gathered in terms of within-group differences, such as students' region of origin, knowledge about or experience with professional psychological services, and the level of acculturation. For example, many studies have shown that acculturation (e.g., Liao et al, 2005) is strongly related to help-seeking attitudes and psychological variables targeted in the present study. It is speculated that these factors might have mediated ethnic group differences as well as differences among Japanese international students in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…The role of acculturation can account separately for the process of adapting to the dominant culture and the process of retaining indigenous cultural orientations (Liao, Rounds, & Klein, 2005). Being involved in Dutch society-but not in a assimilate way (see La Fromboise, Coleman, & Gerton, 1993)-may determine considerably the attitude toward health care and the time before taking action.…”
Section: Discussionmentioning
confidence: 99%
“…In these cultural contexts, excessive self-disclosure and strong emotional expression are devalued because they are regarded as disruptive acts against collective harmony and personal and family honor. Evidence suggests that Asian American college students have greater self-concealment than European American college students (Masuda et al 2009a) and that self-concealment is more negatively related to attitudes toward seeking professional psychological services for Asian and Asian American students (Liao et al 2005).…”
mentioning
confidence: 99%